The occurrence of Ochratoxin (A) in soft wheat and its products under milling conditions used in some mills in Tripoli region - Ellafi, Amar M.; Zeegal, Salem S. (Al-Mukhtar Journal of Sciences, 2018)
This research aimed at detecting the presence of Ochratoxin A (OTA) in common wheat and its products (flour/bran) in some mills in the area of Tripoli. 96 samples of wheat and its products were collected from three mills at the wheat storage, screening and cleaning, flour production, and bran separation. Alkali method and a solid phase column (SPE 18) were applied to extract the poison and clean the extract respectively, and (HPLC) to detect and estimate OTA with quantifications level and the recovery of 0.025 µg/kg and 94% respectively. The results showed that 91% of the (uncleaned) wheat samples were contaminated with OTA, with concentrations ranging from 0.7-12.4 µg/kg and an average of 2.6 µg/kg. The percentage of contamination in the cleaned wheat reached 75% with concentrations ranging from 0.6 to 3.5 µg/kg and an average of 1.9 µg/kg. The toxins presence in flour decreased by 46% and the concentration level ranged between 0.5 and 1.1 µg/kg, with an average of 0.7 µg/kg. Contrary, the percentage of contaminated bran samples went up to 88% with a concentration level of 0.9 to 2.1 7 µg/kg and an average of 1.19 µg/ kg respectively. 84% of wheat samples did not exceed the OTA limit of 5 µg/kg as set by the Libyan Standard. Also, the average OTA concentration in all flour samples was below the limit of 3 µg/kg set by the Libyan Standard. Milling led to a significant reduction of 46% of the presence of OTA in flour. The average concentration of the toxin in the flour also dropped by 73%. The statistical analysis at a confidence level of 99 showed significant differences in OTA presence between each of: the raw, cleaned wheat, and flour/bran. It was concluded that present wheat handling practices should be corrected as well as tightening of the inspection of wheat in the studied mills.